CHARACTERIZATION OF DRUGS ENCAPSULATED INTO MESOPOROUS SILICA - BUDIMAN, ARIF (International Journal of Applied Pharmaceutics, 2019)
Solubility of the drug has a strong influence to achieve higher bioavailability of the drug in systemic circulation. More than 70% NCEs (new chemical entities) are hydrophobic, and practically difficult into solid formulation due to their poor water solubility. Mesoporous silicas (MSP) have been used for drug delivery system, especially for poorly water-soluble drugs. Encapsulation and interaction of drugs in MSP can enhance the delivery and maintain the stability of the drug. However, the characterization of the drug in MSP is necessary to confirm its molecular state. In this review, we present an overview of reports related to the characterization of drug encapsulated into MSP. Encapsulation of drugs in MSP can prevent recrystallization of drugs due to its inhibition of crystal nucleation. A porous material in MSP can maintain the drug in a physically stable amorphous state. The preventing of drug crystallization in MSP can enhance the solubility and the dissolution rate of drug. Therefore, in this work, attempts have been made to understand the molecular state of the drug in MSP. The physicochemical characterization of drug by transmission electron microscopy (TEM), scanning electron microscope (SEM), differential scanning calorimetry (DSC), fourier-transform infrared spectroscopy (FTIR), powder x-ray diffraction (PXRD) and thermogravimetric analysis (TGA) were discussed. The effect of solvent and methods of drug loading and the effect of the shape of MSP on release profiles are also presented. Overall, this review provides information about the characterization of drug encapsulated into MSP which will be useful in pharmaceutical formulation development.